An indole-based aerogel for enhanced removal of heavy metals from water via the synergistic effects of complexation and cation–π interactions. Issue 2 (12th December 2018) - Yang, Peng; Yang, Li; Wang, Yan; Song, Lixian; Yang, Junxiao; Chang, Guanjun
Abstract : A novel indole-based aerogel (4-HIFA) has been obtained by the condensation of 4-hydroxyindole and formaldehyde via sol–gel technology, which proceeds easily by acid catalysis in one pot. Abstract : A novel indole-based aerogel (4-HIFA) has been obtained by the condensation of 4-hydroxyindole and formaldehyde via sol–gel technology, which proceeds easily by acid catalysis in one pot. Taking advantage of the synergistic effects of the complexation and cation–π interactions of the hydroxyl and indole groups with heavy metals, the 4-HIFA exhibits enormous capacities for Ni 2+ (∼240 mg g −1 ), Cu 2+ (∼265 mg g −1 ), Cr 3+ (∼92 mg g −1 ) and Zn 2+ (∼125 mg g −1 ), a selectivity order of Ni 2+ > Cu 2+ > Cr 3+ > Zn 2+, and a very high distribution coefficient ( K d ) of ∼10 5 mL g −1 which place it at the top of materials known for such removal. Furthermore, the adsorptions for all of the four ions reach equilibrium within ∼5 min. As an efficient, low-cost and renewable adsorbent, 4-HIFA is thus promising for use in the processing of large amounts of sewage.